Penggunaan Metode Langsung untuk Meningkatkan Keterampilan Berbicara pada Siswi Kelas Delapan di Kelas Bahasa Madrasah Tsanawiyah Perguruan Mu’allimat Cukir Jombang - Muflihatul Musyarofah (STIKes Ibnu Sina Ajibarang, 2023)
This research is to use the direct method by introducing the vocabulary first and then memorizing and practicing, starting from learning to use this method, the students of the eighth class in the language department of the Islamic Intermediate School Perguruan Mu’allimat of Cukir Jombang are more or less able to master the vocabulary and understand some common vocabulary in the Qur'an so that they can Who can communicate well. The research questions are: How to apply the speech skill to the students of the eighth class in the language department of the Islamic Intermediate School Perguruan Mu’allimat of Cukir Jombang, and how to use the direct method to improve the speaking skill of students in this class, and what are the factors that inhibit and support the use of the direct method to improve the speaking skill of students in this class. The research method is the research approach that the researcher uses in this research, I mean the qualitative approach, and it is the research that obtains results or discoveries. As for the results of the research, they are the following: (1) Applying activities to improve the speaking skill of students for example, when learning a speaking skill, the way the teacher improves the speaking skill of the students is by memorizing vocabulary from there they will be given real items, for example Related to school equipment or facilities, the student should pay attention to real objects, eg bags, paper and books in class. Then the student reads Arabic from the object. You can also guess the picture or something else. 2) Using the direct method to improve speaking skill Briefly explain the use of the direct method to one of the students, Moledet Al-Farika Ainy, explaining that the teacher teaches through: Again, then students follow along, students initiate conversations between other students and memorize them. After everything is memorized, students are paired with their bench mates and practice ahead. (3) The inhibitory and supportive factors in using the direct method to improve speaking skill. The following are: the inhibiting factors, which are the environment that does not always use the Arabic language when communicating, the limitations of teaching aids such as laboratories and liquid crystal displays (LCD/Liquid Crystal Display), because the number of students is not comparable to these tools, there is a foreign language that students do not understand, the lack of time to learn the language Arabic. The supporting factors are there are teaching aids such as books and projectors, there is an interest in students to learn the Arabic language more deeply, the enthusiasm for learning increases among students, the teacher controls the class so that students are interested in participating in learning.